Neutron Stars and Black Holes: Insights from Modified and EiBI Gravity Models - Shafeeque, Muhammed (My University, 2026)
This thesis investigates the structure and properties of compact astrophysical objects—neutron stars and black holes—within both general relativity and modified gravity frameworks. Using a combination of analytical methods and numerical computation, the work addresses critical issues such as the equation of state at extreme densities, the role of alternative gravity theories in supporting massive stars, and the existence of scalar fields around black holes in light of classical no-hair theorems.
Nandy, Malay Kumar